Pengembangan Wilayah Desa melalui Peningkatan Ekonomi Masyarakat Kampung Arar: Studi Kegiatan Pembuatan Produk Udang Rebon - Rifqah, Nabila Nur; Ibal, La; Masniar, Masniar; Murni, Murni; Abu, Nur; Tajuddin, Tamrin; Abubakar, Endang (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The development of rural areas remains a key focus within national policy efforts to enhance community welfare by leveraging local resources. Arar Village, located in Mayamuk District, Sorong Regency, Southwest Papua, possesses abundant marine resources, particularly rebon shrimp, that have yet to be fully harnessed. This community engagement initiative was designed to stimulate the village economy by providing hands-on training in producing rebon shrimp chili sauce. The program involved several stages: initial preparation, community outreach, skills training, and ongoing production support. Throughout the process, participants—primarily women and local youth—demonstrated remarkable enthusiasm and quickly adapted to the techniques required to create hygienic and attractively packaged products. The resulting chili sauce has the potential to serve as a signature culinary product for Arar Village and may pave the way for new entrepreneurial ventures. Beyond technical skills, the program fostered increased household income and reinforced the village’s unique economic identity, all rooted in the sustainable use of local potential.